Pandangan Islam Tentang Pilihan Kehidupan Wanita Karir - Nova Yanti Maleha (An Nisa'a, 2018)
The number of career women who postpone marriage in order to pursue a desirable career. Female factors in delaying marriage, namely: pursuing a career, fulfilling the wishes of parents, social status in society, Do not want to be bound or want to be free, job requirements, residential environment, single life priority or personal desire, culture in society, get a life partner after work. In addition, there are some positive and negative impacts of single life. In the perspective of Islamic law delaying marriage in pursuit is generally contrary to Islamic law. Because women in Islam function as housewives.